CITY BRANDING SHIFT ANALYSIS (CASE STUDY: MADIUN CITY) - Erdiana, Luthfi Widad; Slamet, Slamet (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to reveal the process of shifting city branding that occurred in Madiun City. The research method used is descriptive qualitative. This study utilized two types of data, namely primary data obtained through non-participant observation in the City of Madiun and interviews with the Tourism Sector of the Department of Culture, Tourism, Youth and Sports of the City of Madiun and stakeholders in the City of Madiun. Meanwhile, secondary data was obtained from studies of government documents and data from the Central Bureau of Statistics. The data analysis technique used is the Miles & Huberman Interactive Model data analysis by testing the validity of the data using technical triangulation, source triangulation and member checking.